PENGEMBANGAN PERANGKAT PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) DENGAN METODE PEMECAHAN MASALAH POLYA PADA MATERI MENYELESAIAKAN PERMASALAHAN YANG BERKAITAN DENGAN SEGIEMPATDI KELAS VII SMP - Nurpitasari, Tika; Suharto, S; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2014)
Abstract.The research purpose are knowing process and result of development of mathematics learning materials by CTL ( Contextual Teaching and Learning) and problem solving with Polya Method. This research was held in SMPN 10 Jember at seventh grade. The topic of this research is resolving problem related to quadrilateral. The research has product namely Lesson Plan, worksheet, and evaluation test.The development of this learning materials refers to Plomp model which has 5 phases. They are phases of preliminary investigation; phase of design; phase of realization or contruction; phase of test, evaluation and revision; and phase of implementation.The learning material is said good if it satisfies 3 criterias. That are validity, practicality, and effectiveness. KeyWords:mathematics learning sets, contextual teaching and learning, problem solving, polya method and resoloving problem related to quadrilateral